Kecenderungan Cinderella Complex: Analisis Korelasional Pola Asuh dan Konsep Diri pada Santriwati - Setiawan, Nugroho Arief; Aisyah, Nur (Al Huwiyah: Journal of Woman and Children Studies, 2024)
Abstract The Cinderella Complex is largely defined as a network of repressed attitudes and worries that, like Cinderella, stop women from using their minds and creativity to the fullest. The occurrence of Cinderella Complex in individuals can be influenced by several factors, namely: parenting style and self-concept. The population in this study were all students at the Tri Bakti Al Ikhlas Islamic Boarding School, totaling 97 people. This research aims to empirically prove the relationship between parenting patterns and self-concept with the tendency to have a Cinderella complex in female students at the Tri Bakti Al Ikhlas Islamic Boarding School. The data used is primary data with data collection techniques using questionnaires. The analytical method in this research is correlation analysis and multiple linear regression. The analytical tool used in this research is the SPSS Version 20 program. The results of this research prove that permissive parenting and self-concept have a positive and very strong relationship with the tendency to have a Cinderella complex in female students. The contribution of the influence of the independent variables (permissive parenting style and self-concept) to the dependent variable (Cinderella complex) was 86.8%, while the remaining 13.2% was influenced or explained by other factors not included in this model.Keywords:  Cinderella Complex, Foster Pattern, Self Conception.